Core Kubernetes - Vyas, Jay; Love, Chris (Manning Publications, 2022)
Take a deep dive into Kubernetes inner components and discover what really powers a Kubernetes cluster. This in-depth guide shines a light on Kubernetes' murky internals, to help you better plan cloud native architectures and ensure the reliability of your systems. To build and operate reliable Kubernetes-based systems, you need to understand what's going on below the surface. Core Kubernetes is an in-depth guide to Kubernetes' internal workings written by Kubernetes contributors Chris Love and Jay Vyas. It's packed with experience-driven insights and advanced techniques you won't find anywhere else. You'll understand the unique security concerns of container-based applications, minimize costly unused capacity, and get pro tips for maximizing performance. Diagrams, labs, and hands-on examples ensure that the complex ideas are easy to understand and practical to apply.